COMPARITIVE ANALYSIS OF AD- HOC AS AGAINST INSTITUTIONAL ARBITRATION (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
The origin of arbitration can be traced back to the resolution of disputes, however, the development of arbitration in various nations comprehends a broader scope. Arbitration is a method of settling conflicts by following a specific set of rules agreed upon by the involved parties, rather than going to court. Both ad hoc and institutional arbitrations are acknowledged as valid methods of resolving disputes. Institutional arbitration is the process of conducting arbitration under the guidance of an organization, following its established set of procedural rules. The institution offers assistance for the execution of the arbitration by appointing arbitrators, providing case management services that include supervising the arbitral process, and offering venues for conducting hearings, etc. There are various distinctions between the two ways of Arbitration which can be seen in the study further.The author has also attempted to classify the reasons why institutional arbitration has not gained popularity in India so far.